Suppression of Reverse Drain-Induced Barrier Lowering in Negative Capacitance FETs Using a Hetero-Metal-Gate Structure - Jae Yeon Park; Seungwon Go; Dong Keun Lee; Seonggeun Kim; Sihyun Kim; Sangwan Kim (IEEE Access, 2025)
In this paper, the reverse drain-induced barrier lowering (RDIBL) in the negative capacitance field-effect transistor (NCFET) is discussed. It is found that the RDIBL is attributed to the increase of barrier height between channel and drain with the higher drain voltage ( $V_{DS}$ ). To address this issue, a hetero-metal-gate negative capacitance field-effect transistor (HM NCFET), which features the metal-gate composed of two different work function materials at source and drain sides, is proposed and its electrical characteristics are analyzed with the help of technology computer-aided design (TCAD) simulation. In contrast to the conventional NCFET, the HM NCFET can efficiently suppress RDIBL from -57 mV/V to -3 mV/V by decreasing the work function of metal-gate at drain side from 4.6 eV to 4.0 eV, while the work function of metal-gate at source side is fixed at 4.6 eV.